STRATEGI PENAGIHAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (PBB-P2) (Studi pada Badan Pelayanan Pajak Daerah Kota Malang Tahun 2013-2017) - Mochammad Haykel Martak (Jurnal Ilmiah Mahasiswa FEB, 2018)
As a result of the issuance of Law No. 28 of 2009 concerning regional taxes and regionallevies, most regional governments have received the transfer of authority for PBB-P2collection from the central government to regional governments. In terms of thistransfer BP2D Malang City is still experiencing obstacles in terms of data collection ofTaxpayers (WP). This research refers to the effectiveness theory which aims todetermine the extent to which the strategies applied by Malang City BP2D in PBB-P2billing. The method of data collection in this study uses a semi-structured survey methodand documentation related to the data needed. Analysis of the data in this study after thedata was collected was condensed to the data which was then presented by taking intoaccount the continuity of the data for conclusions. The results showed that the thestrategy for optimizing PAD revenues through PBB-P2 collection was successful.